Pengaruh Struktur Modal Terhadap Kinerja Perusahaan Telekomunikasi Dunia - Fauzi, Rizal Ahmad; Achsani, Noer Azam; Andati, Trias; Anggaraeni, Lukytawati (School of Business, Bogor Agricultural University (SB-IPB), 2022)
This study aim to describe the capital structure of the world telecommunications companies and analyze the effect of capital structure on company performance. The sample used is 205 telecommunication companies listed on the world capital market covering 62 countries covering periods year 2010-2020. The capital structure proxied by debt on asset ratio, both long term ratio and short term ratio, while company performance represent by return on asset. Data analysis using dynamic data panel with generalized methods of moment methods. Data show that capital structure of world telecommunication firm is increase where the long term increase higher than short term. The estimation result indicated that capital structure of telecommunication firm both longterm and shorterm has negative impact to firm performance. Firm size indicated has negative impact to performance, on contrary, firm growth has positive relationship with telecommunication firm perfomance. Keywords: debt ratio, return on assets, generalized methods of moments (GMM), telecommunication companies, telecommunication firm perfomance